Juliette Dissel (1902-1962) : la passion du théâtre occitan - Joëlle Ginestet (Revue des Langues Romanes)
In 1924-1925, Aimée Peine (Juliette Dissel) a young woman born near Castelnaudary (Aude) created the Théâtre d’Oc. Guided by two mentors, abbot Salvat from the Collègi d’Occitania and Armand Praviel a journalist, book reviewer and Jòcs Florals Academy maintainer, she used to perform during occitan poetry shows and was mainly known for his moving « poems recitation ». Influenced by Léon Chancerel theatrical projects, she settled down in Toulouse just before the second world war. Supported by instigators of the Révolution nationale régionaliste to give work to her actors, she was then abandoned by almost everybody until she died in Pessac (Gironde) in 1962.